Unravelling a Rare Conundrum: Enigmatic Cyst Over a Clubfoot - Talak Doddabasappa, Mruthyunjaya; Ugrappa , Harish; Iqbal, Roshan; Kumar, Akash (Scripta Medica, 2025)
Acral skin has been found to have a different aetiology for epidermal cysts, also referred to as epidermal inclusion cysts, epidermoid cysts and infundibular cysts, then non-acral skin. They primarily affect hairy areas such as the face, scalp, neck and trunk. On the palms and soles, where there are no hair follicles, epidermal cysts sporadically develop. According to a number of publications, the development of epidermal cysts on acral skin differs from that on non-acral skin. Most of the epidermal cysts on the sole had parakeratosis and a localised absence of granular layer, at least on the upper part of the cyst wall, when examined under a microscope. Compact orthokeratotic material made up the majority of the cyst content of the sole's epidermal cysts. The pathophysiology of solitary epidermal cysts, specifically invagination of surface epidermis, may account for these pathological features. According to presented research, the lone epidermal cyst is regarded as a genuine traumatic epidermal inclusion cyst. On the palms and soles, epidermal cysts might be mistaken for calluses or warts. Inappropriate treatment may result from this misdiagnosis.
Keywords: Epidermal cysts; Clubfoot; Congenital